Gut microbiota is associated with persistence of longer-term BNT162b2 vaccine immunogenicity - Ng, Ho Yu; Liao, Yunshi; Cheung, Ching Lung; Zhang, Ruiqi; Chan, Kwok Hung; Seto, Wai-Kay; Leung, Wai K.; Hung, Ivan F. N.; Lam, Tommy T. Y.; Cheung, Ka Shing (Frontiers in Immunology, 2025)
IntroductionBNT162b2 immunogenicity wanes with time and we investigated association between gut microbiota and longer-term immunogenicity.MethodsThis cohort study prospectively recruited adult BNT162b2 two-dose recipients from three vaccination centers in Hong Kong. Blood samples were collected at baseline and day 180 after first dose, and tested for neutralizing antibodies (NAb) against receptor-binding domain (RBD) of wild type SARS-CoV-2 virus using chemiluminescence immunoassay. Shotgun DNA metagenomic sequencing was performed to characterize baseline stool microbiome. Baseline metabolites were measured by gas and liquid chromatography-tandem mass spectrometry (GC-MS/MS and LC-MS/MS). Primary outcome was persistent high NAb response (defined as top 25% of NAb level) at day 180. Putative bacterial species and metabolic pathways were identified using linear discriminant analysis [LDA] effect size analysis. Multivariable logistic regression adjusting for clinical factors was used to derive adjusted odds ratio (aOR) of outcome with bacterial species and metabolites.ResultsOf 242 subjects (median age: 50.2 years [IQR:42.5-55.6]; male:85 [35.1%]), 61 (25.2%) were high-responders while 33 (13.6%) were extreme-high responders (defined as NAb≥200AU/mL). None had COVID-19 at end of study. Ruminococcus bicirculans (log10LDA score=3.65), Parasutterella excrementihominis (score=2.82) and Streptococcus salivarius (score=2.31) were enriched in high-responders, while Bacteroides thetaiotaomicron was enriched in low-responders (score=-3.70). On multivariable analysis, bacterial species (R. bicirculans–aOR: 1.87, 95% CI: 1.02-3.51; P. excrementihominis–aOR: 2.2, 95% CI: 1.18-4.18; S. salivarius–aOR: 2.09, 95% CI: 1.13-3.94) but not clinical factors associated with high response. R. bicirculans positively correlated with most metabolic pathways enriched in high-responders, including superpathway of L-cysteine biosynthesis (score=2.25) and L-isoleucine biosynthesis I pathway (score=2.16) known to benefit immune system. Baseline serum butyrate (aOR:10.00, 95% CI:1.81-107.2) and isoleucine (aOR:1.17, 95% CI:1.04-1.35) significantly associated with extreme-high vaccine response.ConclusionCertain gut bacterial species, metabolic pathways and metabolites associate with longer-term COVID-19 vaccine immunogenicity.